PENGARUH MOTIVASI INTRINSIK DAN KOMPENSASI TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi pada Karyawan Kantor PT. Telekomunikasi Indonesia Tbk. Divisi Regional IV Wilayah Jateng dan DIY ) - Felinda, Brigitta Vina; Nugraheni, Rini (Faculty of Economics and Business Diponegoro University, 2016)
This study aims to analyze the effect of intrinsic motivation and compensation on the employee performance with work satisfaction as intervening variable. However employee performance is the most important asset of all, there was a problem of decreasing employee performance at PT Telkomunikasi Indonesia Divisi Regional IV Jateng and DIY. Research gap from the previous research also becomes the background of this research.The data in this research were collected through questionnaires that implemented to 76 permanent employees of PT Telekomunikasi Indonesia Divisi Regional IV Jateng and DIY. Analysis of the data in this research using Sobel test to test the effects of mediation. The program data using SPSS 21 program.This research indicated that intrinsic motivation have positive and significant effect on job satisfaction but its not significant on employee performance, compensation have positive and significant effect on work satisfaction and employee performance and job satisfaction have positive and significant influence on employee performance. In addition, work satisfaction is proven as mediator relationship between intrinsic motivation and compensation on performance. With Total Determination test, intrinsic motivation, compensation and work satisfaction also give 69,48% contribution to the variety of employee peformance